Forestry and forest Products in the German Democratic Republic - Schuster, Erhard (Indian Forester, 1963)
The temperate forests of the GDR consist mainly of pine, spruce, beech, and oak. 27.3% of the country are wooded. Silviculture and management take place according to modern concepts. The wood utilization is highly mechanized and intensive. It is decreasing during the last years due to the heavy over-exploitation before, during, and shortly after the World War II. To the same extent, wood imports are increasing. There is a well-developed wood-based industry embracing all kinds of wood processing. Because of the limited resources, the wood consumption is done economically, but in the main items it is higher than the world average. Spruce bark and pine resin are the most important minor forest products. The forest organization meets the requirements of the socialist planned economy. The Government spends high amounts for the forest education and the research work